Effects of case-load size on the process of care of patients with severe psychotic illness. Report from the UK700 trial. - Burns, T; Fiander, M; Kent, A; Ukoumunne, O; Byford, S; Fahy, T; Kumar, K (2000)
BACKGROUND: Studies of intensive case management (ICM) for patients with psychotic illnesses have produced conflicting results in terms of outcome. Negative results have sometimes been attributed to a failure to deliver differing patterns of care. AIMS: To test whether the actual care delivered in a randomised clinical trial of ICM v. standard case management (the UK700 trial) differed significantly. METHOD: Data on 545 patients' care were collected over 2 years. All patient contacts and all other patient-centred interventions (e.g. telephone calls, carer contacts) of over 15 minutes were prospectively recorded. Rates and distributions of these interventions were compared. RESULTS: Contact frequency was more than doubled in the ICM group. There were proportionately more failed contacts and carer contacts but there was no difference in the average length of individual contacts or the proportion of contacts in the patients' homes. CONCLUSIONS: The failure to demonstrate outcome differences in the UK700 study is not due to a failure to vary the treatment process. UK standard care contains many of the characteristics of assertive outreach services and differences in outcome may require that greater attention be paid to delivering evidence-based interventions.